2004
DOI: 10.1111/j.1365-2044.2004.03609.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressures within air‐filled tracheal cuffs at altitude – an in vivo study

Abstract: SummaryAeromedical transport of mechanically ventilated critically ill patients is now a frequent occurrence. However, the performance of the air filled tracheal tube cuff at altitude has not been studied in vivo. We measured the tracheal cuff pressures at ground level and at 3000 ft, in 10 intubated patients. With air providing the seal in the cuff the mean rise in cuff pressure was 23 cmH 2 O, which took the pressures above the critical perfusion pressure of the tracheal mucosa. This could lead to tracheal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The helicopter flew at a maximum altitude of 3,000 feet above sea level, with an average altitude of 1,931 feet and an average increase in altitude of 1,420 feet. The studies reporting clinically significant changes in tube cuff pressure reported these results at altitudes of at least 3,000 feet 1, 17. In this study, the mean altitude was only 1,931 feet with only one air-medical mission reporting a maximum altitude of 3,000 feet above sea level.…”
Section: Discussionmentioning
confidence: 50%
“…The helicopter flew at a maximum altitude of 3,000 feet above sea level, with an average altitude of 1,931 feet and an average increase in altitude of 1,420 feet. The studies reporting clinically significant changes in tube cuff pressure reported these results at altitudes of at least 3,000 feet 1, 17. In this study, the mean altitude was only 1,931 feet with only one air-medical mission reporting a maximum altitude of 3,000 feet above sea level.…”
Section: Discussionmentioning
confidence: 50%
“…The effect of altitude on air-filled tracheal tube cuffs is well documented with recommendations to evacuate air from the cuffs after increases in altitude of as little as 2000 -3000 feet (10,11). However, we were unable to find documentation of the effect altitude has on the LMA cuff.…”
Section: Introductionmentioning
confidence: 61%
“…Had the pressures not been normalized the risk of tracheal injury might have been even higher. Several papers have demonstrated that ETTCP is affected by altitude changes23 when patients are transported by aeromedical transport modes 2427. This analysis of patients presenting for HEMS transport demonstrated that the majority began with pressure outside the safe range.…”
Section: Discussionmentioning
confidence: 94%